2015
DOI: 10.1186/s12885-015-1044-0
|View full text |Cite
|
Sign up to set email alerts
|

Melan-A/MART-1 immunity in a EWS-ATF1 translocated clear cell sarcoma patient treated with sunitinib: a case report

Abstract: BackgroundClear cell sarcoma (CCS), initially named malignant melanoma of soft parts, is an aggressive soft tissue sarcoma (STS) that, due to MITF activation, shares with melanoma the expression of melanocyte differentiation antigens. CCS is poorly sensitive to chemotherapy. Multi-kinase inhibitors have been used as therapeutic agents. In the case we report here, treatment with sunitinib induced a long-lasting clinical response that was associated with an immune activation directed against Melan-A/MART-1 antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Targeted therapy drugs belonging to the anti-angiogenic family, such as sunitinib and pazopanib, have been used for different STS histologies, including solitary fibrous tumors (SFT) and clear cell sarcomas (CSC). In these simple karyotype STSs, we have shown that these drugs modulate systemic and local host immune components [ 55 , 56 , 57 ] and convert the immune TME from “cold” to “hot”. Indeed, sunitinib, by virtue of its effect of the tumor vasculature, promoted an influx of T cells within the previously T cell desert tumor bed.…”
Section: Translational Aspects Of Genetic Immunity Interactionmentioning
confidence: 99%
“…Targeted therapy drugs belonging to the anti-angiogenic family, such as sunitinib and pazopanib, have been used for different STS histologies, including solitary fibrous tumors (SFT) and clear cell sarcomas (CSC). In these simple karyotype STSs, we have shown that these drugs modulate systemic and local host immune components [ 55 , 56 , 57 ] and convert the immune TME from “cold” to “hot”. Indeed, sunitinib, by virtue of its effect of the tumor vasculature, promoted an influx of T cells within the previously T cell desert tumor bed.…”
Section: Translational Aspects Of Genetic Immunity Interactionmentioning
confidence: 99%
“…Awareness of this potential pitfall is important, because the clinical behavior of malignant gastrointestinal neuroectodermal tumor and other oncocytic/granular cell tumors of the stomach is quite different, and as there may be some role for targeted therapy in tumors showing EWSR1-ATF1 fusion, which activates potentially targetable downstream effectors including IGFR1, MET, MITF and PDGFR(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Recent progression in treatments including molecular targeted therapy and immunotherapy for several malignancies, especially for malignant melanoma (20) which has many similarities to CCS (21)(22)(23)(24)(25), has therefore attracted considerable attention for CCS. Although a number of reports indicate the possible efficacy of new therapeutic agents against CCS (23)(24)(25)(26)(27)(28)(29), most are case reports of single cases or a very small number of cases. Therefore, establishing the evidence of efficacy of these agents against CCS, both in basic research and clinically are required.…”
Section: Discussionmentioning
confidence: 99%